Polyether-ether-ketone composite material, preparation method and application
By combining modified zinc oxide whiskers and sulfonated polyether ether ketones, the problem of poor interface bonding force between zinc oxide whiskers and resin base in polyether ether ketone materials is solved, and the conductivity and mechanical properties are improved. The preparation of High-strength antistatic composite material.
Patent Information
- Application Number
- CN202411373190.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-07
AI Technical Summary
The interface bonding force between zinc oxide whiskers and resin base in existing polyether ether ketone materials is poor, resulting in insufficient improvement in conductivity.
Modified zinc oxide whiskers and sulfonated polyether ether ketones are used to combine modified zinc oxide whiskers through amino coupling agents and introduce sulfonic acid groups on the polyether ether ketone main chain to enhance zinc oxide whiskers and polyether The wetting and bonding power of the etherketone resin, and glass fibers and aramid fibers are added to enhance the mechanical properties of the material.
The dispersion uniformity and comprehensive performance of zinc oxide whiskers in polyether ether ketone resin are significantly improved, the conductivity and mechanical properties of the material are enhanced, and the preparation of high-strength antistatic composite materials are realized.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer materials, and in particular to a polyetheretherketone composite material, a preparation method and application thereof. Background Art
[0002] Polyetheretherketone resin is a highly crystalline aromatic linear thermoplastic specialty resin. It has the heat resistance and chemical stability of aromatic thermosetting resins and the easy processing of thermoplastic resins. It has excellent comprehensive performance and has been widely used in the automotive, aerospace, electrical and electronic, chemical, mechanical and medical fields. Since polyetheretherketone has a high volume resistivity and cannot meet the different needs of the industry, it is necessary to improve the conductivity of polyetheretherketone.
[0003] Zinc oxide whisker (T-ZnOw) is the only whisker with a three-dimensional structure discovered since the 1940s. Due to its unique three-dimensional four-needle structure, high strength and semiconductor properties, it is considered to be an excellent filler and can be widely used as a conductive material for metals, alloys, ceramics, rubber and other materials. However, T-ZnOw is a functional inorganic filler with a high-energy surface, which is easy to aggregate into agglomerates. The hydrophilic and oleophobic surface is not conducive to uniform dispersion in organic solvents. At the same time, the interface bonding strength with the resin base material is poor, and defects are easily generated, resulting in decreased material performance. Summary of the invention
[0004] The purpose of the present invention is to provide a polyetheretherketone composite material, a preparation method and an application thereof, which solves the technical problem in the prior art that zinc oxide whiskers improve the conductivity of polyetheretherketone, that is, the interface bonding strength with the resin base material is poor.
[0005] The present invention provides the following scheme:
[0006] In a first aspect, the present invention describes a polyetheretherketone composite material, comprising the following components in parts by weight:
[0007] 50-80 parts of polyetheretherketone resin, 5-25 parts of modified zinc oxide whisker, 5-25 parts of sulfonated polyetheretherketone, 5-30 parts of glass fiber, 5-30 parts of aramid fiber, 0.1-1 parts of lubricant, 0.1-1 parts of antioxidant, 0.1-1 parts of dispersant and 0.1-1 parts of coupling agent.
[0008] Preferably, the following components are included in parts by weight:
[0009] 60-70 parts of polyetheretherketone resin, 10-15 parts of modified zinc oxide whisker, 5-10 parts of sulfonated polyetheretherketone, 5-20 parts of glass fiber, 5-20 parts of aramid fiber, 0.1-1 parts of lubricant, 0.1-1 parts of antioxidant, 0.1-1 parts of dispersant and 0.1-1 parts of coupling agent.
[0010] Preferably, the modified zinc oxide whisker is prepared by modifying zinc oxide whisker with a coupling agent; wherein the coupling agent is a coupling agent containing an amino group.
[0011] Preferably, the polyetheretherketone resin has a crystallinity of 20-40% and a melt index of 20-100 g / 10 min at 5 kg / 380°C.
[0012] Preferably, the modified zinc oxide whisker has a root diameter of 0.5-5 μm, an aspect ratio of (10-40):1, and an apparent density of 0.1-0.3 g / cm 3 .
[0013] Preferably, the sulfonation degree of the sulfonated polyetheretherketone is 40-50%.
[0014] Preferably, the fiber glass is short-cut alkali-free fiber glass with a diameter of 10-13 μm, an average length of 0.1-5 mm, and a surface coated with a silane coupling agent;
[0015] The aramid fiber is aramid 1313, has a diameter of 10-15 μm, an average length of 0.1-3 mm, and is coated with a silane coupling agent.
[0016] Preferably, the lubricant is one or more of calcium stearate, PETS, EBS, and ethylene wax;
[0017] The antioxidant is one or more of 1,3,5-tris(3,5-di-tert-butyl, 4-hydroxybenzyl)-s-triazine, 4,4'-thiobis(6-tert-butyl-3-methylphenol), and di(octadecyl)thiodipropionate;
[0018] The dispersant is one or more of montan wax, oxidized polyethylene wax, silicone powder, etc.;
[0019] The coupling agent is a silane coupling agent.
[0020] In a second aspect, the present invention describes a method for preparing a polyetheretherketone composite material, comprising the following steps:
[0021] S1: Modifying zinc oxide whiskers with an amino coupling agent to obtain modified zinc oxide whiskers;
[0022] S2: Sulfonating the polyetheretherketone to obtain sulfonated polyetheretherketone;
[0023] S3: The prepared modified zinc oxide whiskers and sulfonated polyetheretherketone are used to prepare conductive polyetheretherketone masterbatch with polyetheretherketone resin, lubricant, antioxidant and dispersant;
[0024] S4: melt-extrude and granulate the prepared conductive polyetheretherketone masterbatch, polyetheretherketone resin, sulfonated polyetheretherketone, glass fiber, aramid fiber, lubricant, antioxidant, dispersant and coupling agent to obtain a polyetheretherketone composite material.
[0025] In a third aspect, the present invention describes an application of a polyetheretherketone composite material, wherein the polyetheretherketone composite material is used in the fields of automobile, aerospace, electrical and electronic, chemical industry, and machinery.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] The polyetheretherketone composite material of the invention adopts polyetheretherketone resin as a substrate and three-dimensional four-needle zinc oxide whiskers as a main conductor. The zinc oxide whiskers are modified to improve the wettability and bonding force between the zinc oxide whiskers and the polyetheretherketone resin material, thereby improving the dispersion uniformity of the zinc oxide whiskers in the polyetheretherketone resin.
[0028] Sulfonated polyetheretherketone (SPEEK) is a modified material that introduces sulfonic acid groups into the main chain of polyetheretherketone (PEEK). This modification allows SPEEK to maintain the excellent physical and chemical properties of PEEK while increasing its hydrophilicity and ion conductivity. Since the molecular structure of sulfonated polyetheretherketone is similar to that of polyetheretherketone resin, except that the sulfonic acid group is introduced, this structural similarity ensures good compatibility between the two, and at the same time, improves the ionic conductivity and chemical corrosion resistance of PEEK.
[0029] The combined use of modified zinc oxide whiskers and sulfonated polyetheretherketone can form a stronger interface connection between inorganic and organic materials and between different organic materials, thereby achieving better dispersibility and higher comprehensive performance, and making a high-strength antistatic polyetheretherketone composite material. And by adding glass fiber and aramid fiber to improve the mechanical properties of the material, the volume resistance of the composite material can be uniform and stable during the molding process such as extrusion and injection molding. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solutions and advantages of the present application clearer, the present application will be further described in detail below. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0031] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, and unless the context clearly indicates other meanings, "multiple" generally includes at least two.
[0032] It should be understood that the term "and / or" used in this article is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0033] It should be understood that, although the terms first, second, third, etc. may be used to describe in the embodiments of the present application, these descriptions should not be limited to these terms. These terms are only used to distinguish the descriptions. For example, without departing from the scope of the embodiments of the present application, the first may also be referred to as the second, and similarly, the second may also be referred to as the first.
[0034] As used herein, the words "if" and "if" may be interpreted as "at the time of" or "when" or "in response to determining" or "in response to detecting", depending on the context. Similarly, the phrases "if it is determined" or "if (stated condition or event) is detected" may be interpreted as "when it is determined" or "in response to determining" or "when detecting (stated condition or event)" or "in response to detecting (stated condition or event)", depending on the context.
[0035] It should also be noted that the term "includes", "comprising" or any other variation thereof is intended to cover non-exclusive inclusion, so that a commodity or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such commodity or device. In the absence of more restrictions, the elements defined by the sentence "comprising a ..." do not exclude the existence of other identical elements in the commodity or device including the elements.
[0036] It should be particularly noted that any symbols and / or numbers in the specification that are not marked in the accompanying drawings are not drawing marks.
[0037] A first aspect of an embodiment of the present invention provides a polyetheretherketone composite material, comprising the following components in parts by weight:
[0038] 50-80 parts of polyetheretherketone resin, 5-25 parts of modified zinc oxide whisker, 5-25 parts of sulfonated polyetheretherketone, 5-30 parts of glass fiber, 5-30 parts of aramid fiber, 0.1-1 parts of lubricant, 0.1-1 parts of antioxidant, 0.1-1 parts of dispersant and 0.1-1 parts of coupling agent.
[0039] The polyetheretherketone composite material of the embodiment of the present invention adopts polyetheretherketone resin as a substrate and three-dimensional four-needle zinc oxide whiskers as a main conductor. The zinc oxide whiskers are modified to improve the wettability and bonding strength between the zinc oxide whiskers and the polyetheretherketone resin material, thereby improving the dispersion uniformity of the zinc oxide whiskers in the polyetheretherketone resin.
[0040] Sulfonated polyetheretherketone (SPEEK) is a modified material that introduces sulfonic acid groups into the main chain of polyetheretherketone (PEEK). This modification allows SPEEK to maintain the excellent physical and chemical properties of PEEK while increasing its hydrophilicity and ion conductivity. Since the molecular structure of sulfonated polyetheretherketone is similar to that of polyetheretherketone resin, except that the sulfonic acid group is introduced, this structural similarity ensures good compatibility between the two, and at the same time, improves the ionic conductivity and chemical corrosion resistance of PEEK.
[0041] The combined use of modified zinc oxide whiskers and sulfonated polyetheretherketone can form a stronger interface connection between inorganic and organic materials and between different organic materials, thereby achieving better dispersibility and higher comprehensive performance, and making a high-strength antistatic polyetheretherketone composite material. And by adding glass fiber and aramid fiber to improve the mechanical properties of the material, the volume resistance of the composite material can be uniform and stable during the molding process such as extrusion and injection molding.
[0042] Preferably, 60-70 parts of polyetheretherketone resin, 5-15 parts of modified zinc oxide whiskers, 5-10 parts of sulfonated polyetheretherketone, 5-20 parts of glass fiber, 5-20 parts of aramid fiber, 0.1-1 part of lubricant, 0.1-1 part of antioxidant, 0.1-1 part of dispersant and 0.1-1 part of coupling agent.
[0043] By adopting the above preferred mass fractions, the obtained polyetheretherketone composite material can have lower volume resistivity and stronger mechanical properties.
[0044] In some embodiments, the modified zinc oxide whisker is prepared by modifying the zinc oxide whisker with a coupling agent, wherein the coupling agent is an amino-containing coupling agent, further an aminosilane coupling agent, such as KH550 (γ-aminopropyltriethoxysilane).
[0045] Aminosilane coupling agents are usually composed of special structures such as primary amino groups (-NH2), secondary amino groups (-NH-) and Si-OR (R is a small molecular group). Due to the presence of free amino groups, they can combine with the sulfonic acid groups in sulfonated polyetheretherketone acid. The two synergistically improve the wettability and bonding between zinc oxide whiskers and polyetheretherketone resin materials, effectively combining zinc oxide whiskers with polyetheretherketone resin, and thus improving the dispersion uniformity of zinc oxide whiskers in polyetheretherketone resin.
[0046] In some embodiments, the polyetheretherketone resin has a crystallinity of 20-40% and a melt index of 20-100 g / 10 min at 5 kg / 380° C.
[0047] In some embodiments, the modified zinc oxide whisker has a root diameter of 0.5-5 μm, an aspect ratio of (10-40):1, and an apparent density of 0.1-0.3 g / cm 3 .
[0048] In some embodiments, the degree of sulfonation of the sulfonated polyetheretherketone is 40-50%.
[0049] The degree of sulfonation refers to the content of ionizable sulfonic acid groups in the polymer. Sulfonated polyetheretherketone within this range, on the one hand, has good proton conductivity, which can improve the ionic conductivity of PEEK; on the other hand, it can maintain good compatibility with PEEK while fully combining with the modified zinc oxide whiskers, so that the synergistic effect of the two can achieve the best effect.
[0050] In some embodiments, the glass fiber is a chopped alkali-free glass fiber with a diameter of 10-13 μm, an average length of 0.1-5 mm, and a surface coated with a silane coupling agent;
[0051] The aramid fiber is aramid 1313, has a diameter of 10-15 μm, an average length of 0.1-3 mm, and is coated with a silane coupling agent.
[0052] In some embodiments, the lubricant is one or more of calcium stearate, PETS, EBS, and ethylene wax; the antioxidant is one or more of 1,3,5-tris(3,5-di-tert-butyl, 4-hydroxybenzyl)-s-triazine, 4,4'-thiobis(6-tert-butyl-3-methylphenol), and di(octadecyl)thiodipropionate; the dispersant is one or more of montan wax, oxidized polyethylene wax, silicone powder, etc.; and the coupling agent is a silane coupling agent.
[0053] A second aspect of an embodiment of the present invention provides a method for preparing the above-mentioned polyetheretherketone composite material, comprising the following steps:
[0054] S1: Modifying zinc oxide whiskers with an amino coupling agent to obtain modified zinc oxide whiskers;
[0055] S2: Sulfonating the polyetheretherketone to obtain sulfonated polyetheretherketone;
[0056] S3: The prepared modified zinc oxide whisker and sulfonated polyetheretherketone are used to prepare a conductive polyetheretherketone masterbatch with polyetheretherketone resin, lubricant, antioxidant, dispersant and coupling agent;
[0057] S4: melt-extrude and granulate the prepared conductive polyetheretherketone masterbatch, polyetheretherketone resin, sulfonated polyetheretherketone, glass fiber, aramid fiber, lubricant, antioxidant, dispersant and coupling agent to obtain a polyetheretherketone composite material.
[0058] Step S1 is specifically as follows: take a certain mass of three-dimensional four-needle zinc oxide whiskers and pre-dry them in a vacuum drying oven at a temperature of 150°C for 4 hours; mix anhydrous ethanol and deionized water in a mass ratio of 3:5; add the dried zinc oxide whiskers and the aforementioned ethanol mixed solution in a beaker, and perform ultrasonic dispersion treatment at room temperature for 1 hour. Then, add a mixed solution of silane coupling agent and anhydrous ethanol in a mass ratio of 1:2 at a uniform speed, adjust the pH to 4 with glacial acetic acid, stir the mixed solution at a speed of 1500r / min for 2 hours, then wash the aforementioned mixed solution with anhydrous ethanol in turn and deliquate it by centrifuge for 3 times, and put the obtained solid matter into a drying oven at 120°C for 2 hours to obtain silane coupling agent modified zinc oxide whiskers. The silane coupling agent is at least one of KH550, KH560, and KH570. Among them, the mass ratio of zinc oxide whiskers to silane coupling agent is 100:(5-10).
[0059] Step S2 is specifically, adding polyetheretherketone with a melt index of 100g / 10min under the condition of 5kg / 380℃ to the pressure vessel, then adding p-chlorophenol and o-dichlorobenzene, heating the container, maintaining the temperature at 150℃, the internal pressure at 5MPa, stirring the mixture for 1h, and forming a uniformly dispersed polyetheretherketone solution. Then slowly cool and reduce the pressure, wait until the pressure drops to 1 atmosphere and the solution temperature drops to room temperature, slowly add 96% concentrated sulfuric acid to the above polyetheretherketone solution for sulfonation reaction, and keep the reaction time at 40℃ for 24h. Then let the solution stand for stratification, extract the thick mixture at the bottom and slowly inject the ice-water mixture to precipitate the solid matter. The obtained solid matter is crushed and sieved through a 50-mesh filter disc, and the solid powder is washed with deionized water several times until the pH value of the solution is 7, and then the solid matter powder obtained by filtration is placed in a 120℃ vacuum drying oven and dried for 4h to obtain sulfonated polyetheretherketone.
[0060] Step S3 specifically comprises putting the polyetheretherketone resin, the modified zinc oxide whisker obtained in step S1, the sulfonated polyetheretherketone obtained in step S2, a lubricant, an antioxidant, and a dispersant into a high-speed mixer to mix the materials evenly, and then using a twin-screw extruder to extrude and granulate to obtain a conductive polyetheretherketone composite material masterbatch, wherein the twin-screw extrusion temperature is 360-380°C, and the extrusion speed is 360r / min.
[0061] The prepared conductive polyetheretherketone composite material masterbatch can be used as a material category with a fixed formula, and the amount of the masterbatch added can be adjusted according to different volume resistance design requirements.
[0062] Step S4 specifically comprises: mixing the polyetheretherketone resin, the conductive polyetheretherketone composite material masterbatch obtained in step S3, glass fiber, aramid fiber, sulfonated polyetheretherketone, lubricant, antioxidant, dispersant and coupling agent uniformly by using a high-speed mixer, and then using a twin-screw extruder to perform composite material modification and granulation, with the twin-screw extrusion temperature of 360-380°C and the extrusion speed of 400r / min to obtain polyetheretherketone composite material resin particles.
[0063] A third aspect of the embodiments of the invention provides an application of the polyetheretherketone composite material in the automotive field.
[0064] Example 1
[0065] The polyetheretherketone composite material of this embodiment includes the following components in parts by weight:
[0066] 60 parts of polyetheretherketone resin, 15 parts of modified zinc oxide whisker, 10 parts of sulfonated polyetheretherketone, 10 parts of glass fiber, 20 parts of aramid fiber, 0.2 parts of lubricant, 0.5 parts of antioxidant, 0.7 parts of dispersant and 0.6 parts of coupling agent.
[0067] In this embodiment, the crystallinity of the polyetheretherketone resin is 30%, and the melting index range is 100g / 10min under the condition of 5kg / 380°C.
[0068] Modified zinc oxide whiskers are prepared by modifying zinc oxide whiskers with silane coupling agent KH550. The root diameter is 0.5-5μm, the aspect ratio is (10-40):1, and the apparent density is 0.2g / cm 3 .
[0069] The degree of sulfonation of the sulfonated polyetheretherketone is 43%.
[0070] The glass fiber is short-cut alkali-free glass fiber with a diameter of 10-13 μm and an average length of 3 mm, and the surface is coated with a silane coupling agent.
[0071] The aramid fiber is aramid 1313, has a diameter of 10-15 μm, an average length of 2 mm, and is coated with a silane coupling agent.
[0072] The lubricant is PETS.
[0073] The antioxidant is dioctadecyl thiodipropionate.
[0074] The dispersant is silicone powder.
[0075] The coupling agent is a silane coupling agent.
[0076] The preparation method of the polyetheretherketone composite material of this embodiment comprises the following steps:
[0077] S1: Take three-dimensional four-needle zinc oxide whiskers and pre-dry them in a vacuum drying oven at a temperature of 150°C for 4 hours; mix anhydrous ethanol and deionized water in a mass ratio of 3:5; add the dried zinc oxide whiskers and the aforementioned ethanol mixed solution into a beaker and perform ultrasonic dispersion treatment at room temperature for 1 hour. Then add a mixed solution of KH550 and anhydrous ethanol in a mass ratio of 1:2 at a uniform speed, adjust the pH to 4 with glacial acetic acid, stir the mixed solution at a speed of 1500r / min for 2 hours, then wash the aforementioned mixed solution with anhydrous ethanol in turn and dehydrate it by centrifuge for 3 times, and put the obtained solid matter into a drying oven at 120°C and dry it for 2 hours to obtain silane coupling agent modified zinc oxide whiskers. Among them, the mass ratio of zinc oxide whiskers to KH550 is 100:5.
[0078] S2: Add polyetheretherketone to the pressure vessel, then add parachlorophenol and o-dichlorobenzene, heat the container, maintain the temperature at 150°C, the internal pressure at 5MPa, stir the mixture for 1h, and form a uniformly dispersed polyetheretherketone solution. Then slowly cool down and reduce the pressure. After the pressure drops to 1 atmosphere and the solution temperature drops to room temperature, slowly add 96% concentrated sulfuric acid to the above polyetheretherketone solution for sulfonation reaction, and maintain the reaction time at 40°C for 24h. Then let the solution stand for stratification, extract the thick mixture at the bottom and slowly inject the ice-water mixture to precipitate the solid matter. The obtained solid matter is crushed and sieved through a 50-mesh filter disc, and the solid powder is washed with deionized water several times until the pH value of the solution is 7, and then the filtered solid matter powder is placed in a 120°C vacuum drying oven and dried for 4h to obtain sulfonated polyetheretherketone. Sulfonated polyetheretherketone with a sulfonation degree of 43% is obtained.
[0079] S3: Put the polyetheretherketone resin, the modified zinc oxide whisker obtained in step S1, the sulfonated polyetheretherketone obtained in step S2, the lubricant, the antioxidant, and the dispersant into a high-speed mixer to mix the materials evenly, and then use a twin-screw extruder to extrude and granulate to obtain a conductive polyetheretherketone composite material masterbatch, wherein the twin-screw extrusion temperature is 360-380°C, and the extrusion speed is 360r / min.
[0080] S4: After uniformly mixing the polyetheretherketone resin, the conductive polyetheretherketone composite material masterbatch obtained in step S3, glass fiber, aramid fiber, sulfonated polyetheretherketone, lubricant, antioxidant, dispersant and coupling agent using a high-speed mixer, the composite material is modified and granulated using a twin-screw extruder. The twin-screw extrusion temperature is 360-380°C and the extrusion speed is 400r / min to obtain polyetheretherketone composite material resin particles.
[0081] Example 2
[0082] The polyetheretherketone composite material of this embodiment includes the following components in parts by weight:
[0083] 70 parts of polyetheretherketone resin, 10 parts of modified zinc oxide whisker, 5 parts of sulfonated polyetheretherketone, 20 parts of glass fiber, 10 parts of aramid fiber, 0.2 parts of lubricant, 0.5 parts of antioxidant, 0.7 parts of dispersant and 0.6 parts of coupling agent.
[0084] The difference between this embodiment and embodiment 1 is:
[0085] The lubricant is calcium stearate.
[0086] The antioxidant is 1,3,5-tris(3,5-di-tert-butyl, 4-hydroxybenzyl)-s-triazine.
[0087] The dispersant is montan wax.
[0088] The types and specifications of other components are the same as those in Example 1, but the mass fractions are different.
[0089] The preparation method of this embodiment is the same as that of embodiment 1.
[0090] Example 3
[0091] The polyetheretherketone composite material of this embodiment includes the following components in parts by weight:
[0092] 50 parts of polyetheretherketone resin, 5 parts of modified zinc oxide whisker, 25 parts of sulfonated polyetheretherketone, 5 parts of glass fiber, 30 parts of aramid fiber, 0.2 parts of lubricant, 0.5 parts of antioxidant, 0.7 parts of dispersant and 0.6 parts of coupling agent.
[0093] The difference between this embodiment and embodiment 1 is:
[0094] The lubricant is EBS.
[0095] The antioxidant is 4,4'-thiobis(6-tert-butyl-3-methylphenol).
[0096] The dispersant is oxidized polyethylene wax.
[0097] The types and specifications of other components are the same as those in Example 1, but the mass fractions are different.
[0098] The preparation method of this embodiment is the same as that of embodiment 1.
[0099] Example 4
[0100] The polyetheretherketone composite material of this embodiment includes the following components in parts by weight:
[0101] 50 parts of polyetheretherketone resin, 25 parts of modified zinc oxide whiskers, 5 parts of sulfonated polyetheretherketone, 30 parts of glass fiber, 5 parts of aramid fiber, 0.1 parts of lubricant, 1 part of antioxidant, 0.1 parts of dispersant and 1 part of coupling agent.
[0102] The difference between this embodiment and embodiment 1 is:
[0103] The lubricant is ethylene wax.
[0104] The antioxidant is 4,4'-thiobis(6-tert-butyl-3-methylphenol).
[0105] The dispersant is oxidized polyethylene wax.
[0106] The types and specifications of other components are the same as those in Example 1, but the mass fractions are different.
[0107] The preparation method of this embodiment is the same as that of embodiment 1.
[0108] Example 5
[0109] The polyetheretherketone composite material of this embodiment includes the following components in parts by weight:
[0110] 80 parts of polyetheretherketone resin, 10 parts of modified zinc oxide whiskers, 5 parts of sulfonated polyetheretherketone, 5 parts of glass fiber, 15 parts of aramid fiber, 1 part of lubricant, 0.1 part of antioxidant, 1 part of dispersant and 0.1 part of coupling agent.
[0111] Except for the change in the mass fractions of the components in this embodiment, the selection of the types and specifications of the other components and the preparation method are the same as those in Example 1.
[0112] Example 6
[0113] The polyetheretherketone composite material of this embodiment includes the following components in parts by weight:
[0114] 60 parts of polyetheretherketone resin, 15 parts of modified zinc oxide whisker, 10 parts of sulfonated polyetheretherketone, 10 parts of glass fiber, 20 parts of aramid fiber, 0.2 parts of lubricant, 0.5 parts of antioxidant, 0.7 parts of dispersant and 0.6 parts of coupling agent.
[0115] The specifications and mass fractions of the components in this embodiment are the same as those in Embodiment 1, except that the degree of sulfonation of the sulfonated polyetheretherketone is 30%.
[0116] In the preparation method of this embodiment, in step S2, the temperature and time of the sulfonation reaction are controlled so that the sulfonation degree of the sulfonated polyetheretherketone is 30%. The remaining steps are the same as those in embodiment 1.
[0117] Comparative Example 1
[0118] The polyetheretherketone composite material of this comparative example comprises the following components in parts by weight:
[0119] 80 parts of polyetheretherketone resin, 15 parts of glass fiber, 20 parts of aramid fiber, 0.2 parts of lubricant, 0.5 parts of antioxidant, 0.7 parts of dispersant and 0.6 parts of coupling agent.
[0120] In this embodiment, the crystallinity of the polyetheretherketone resin is 30%, and the melting index range is 100g / 10min under the condition of 5kg / 380°C.
[0121] The glass fiber is short-cut alkali-free glass fiber with a diameter of 10-13 μm and an average length of 3 mm, and the surface is coated with a silane coupling agent.
[0122] The aramid fiber is aramid 1313, has a diameter of 10-15 μm, an average length of 2 mm, and is coated with a silane coupling agent.
[0123] The lubricant is PETS.
[0124] The antioxidant is dioctadecyl thiodipropionate.
[0125] The dispersant is silicone powder.
[0126] The coupling agent is a silane coupling agent.
[0127] The preparation method of the polyetheretherketone composite material of this comparative example is: after the polyetheretherketone resin, glass fiber, aramid fiber, lubricant, antioxidant, dispersant and coupling agent are uniformly mixed by a high-speed mixer, a twin-screw extruder is used to modify and granulate the composite material, the twin-screw extrusion temperature is 360-380°C, and the extrusion speed is 400r / min, to obtain polyetheretherketone composite material resin particles.
[0128] Comparative Example 2
[0129] The polyetheretherketone composite material of this comparative example comprises the following components in parts by weight:
[0130] 75 parts of polyetheretherketone resin, 10 parts of zinc oxide whisker, 10 parts of glass fiber, 20 parts of aramid fiber, 0.2 parts of lubricant, 0.5 parts of antioxidant, 0.7 parts of dispersant and 0.6 parts of coupling agent.
[0131] In this embodiment, the crystallinity of the polyetheretherketone resin is 30%, and the melting index range is 100g / 10min under the condition of 5kg / 380°C.
[0132] The root diameter of zinc oxide whiskers is 0.5-5μm, the aspect ratio is (10-40):1, and the apparent density is 0.2g / cm 3 .
[0133] The glass fiber is short-cut alkali-free glass fiber with a diameter of 10-13 μm and an average length of 3 mm, and the surface is coated with a silane coupling agent.
[0134] The aramid fiber is aramid 1313, has a diameter of 10-15 μm, an average length of 2 mm, and is coated with a silane coupling agent.
[0135] The lubricant is PETS.
[0136] The antioxidant is dioctadecyl thiodipropionate.
[0137] The dispersant is silicone powder.
[0138] The coupling agent is a silane coupling agent.
[0139] The preparation method of the polyetheretherketone composite material of this comparative example comprises the following steps:
[0140] S1: Put polyetheretherketone resin, zinc oxide whisker, lubricant, antioxidant and dispersant into a high-speed mixer to mix the materials evenly, and then use a twin-screw extruder to extrude and granulate to obtain a conductive polyetheretherketone composite material masterbatch, wherein the twin-screw extrusion temperature is 360-380°C and the extrusion speed is 360r / min.
[0141] S2: After uniformly mixing the polyetheretherketone resin, the conductive polyetheretherketone composite material masterbatch obtained in step S1, glass fiber, aramid fiber, sulfonated polyetheretherketone, lubricant, antioxidant, dispersant and coupling agent using a high-speed mixer, the composite material is modified and granulated using a twin-screw extruder. The twin-screw extrusion temperature is 360-380°C and the extrusion speed is 400r / min to obtain polyetheretherketone composite material resin particles.
[0142] Comparative Example 3
[0143] The polyetheretherketone composite material of this comparative example comprises the following components in parts by weight:
[0144] 75 parts of polyetheretherketone resin, 10 parts of sulfonated polyetheretherketone, 10 parts of glass fiber, 20 parts of aramid fiber, 0.2 parts of lubricant, 0.5 parts of antioxidant, 0.7 parts of dispersant and 0.6 parts of coupling agent.
[0145] In this embodiment, the crystallinity of the polyetheretherketone resin is 30%, and the melting index range is 100g / 10min under the condition of 5kg / 380°C.
[0146] The degree of sulfonation of the sulfonated polyetheretherketone is 43%.
[0147] The glass fiber is short-cut alkali-free glass fiber with a diameter of 10-13 μm and an average length of 3 mm, and the surface is coated with a silane coupling agent.
[0148] The aramid fiber is aramid 1313, has a diameter of 10-15 μm, an average length of 2 mm, and is coated with a silane coupling agent.
[0149] The lubricant is PETS.
[0150] The antioxidant is dioctadecyl thiodipropionate.
[0151] The dispersant is silicone powder.
[0152] The coupling agent is a silane coupling agent.
[0153] The preparation method of the polyetheretherketone composite material of this comparative example comprises the following steps:
[0154] S1: Add polyetheretherketone to a pressure vessel, then add parachlorophenol and o-dichlorobenzene, heat the container, maintain the temperature at 150°C, the internal pressure at 5MPa, stir the mixture for 1h, and form a uniformly dispersed polyetheretherketone solution. Then slowly cool down and reduce the pressure. After the pressure drops to 1 atmosphere and the solution temperature drops to room temperature, slowly add 96% concentrated sulfuric acid to the above polyetheretherketone solution for sulfonation reaction, and maintain the reaction time at 40°C for 24h. Then let the solution stand for stratification, extract the thick mixture at the bottom and slowly inject the ice-water mixture to precipitate the solid matter. The obtained solid matter is crushed and sieved through a 50-mesh filter disc, and the solid powder is washed with deionized water several times until the pH value of the solution is 7, and then the filtered solid matter powder is placed in a 120°C vacuum drying oven and dried for 4h to obtain sulfonated polyetheretherketone. Sulfonated polyetheretherketone with a sulfonation degree of 43% is obtained.
[0155] S2: Put the polyetheretherketone resin and the sulfonated polyetheretherketone obtained in step S1, lubricant, antioxidant and dispersant into a high-speed mixer to mix the materials evenly, and then use a twin-screw extruder to extrude and granulate to obtain a conductive polyetheretherketone composite material masterbatch, wherein the twin-screw extrusion temperature is 360-380°C and the extrusion speed is 360r / min.
[0156] S3: After the polyetheretherketone resin, the conductive polyetheretherketone composite material masterbatch obtained in step S2, glass fiber, aramid fiber, sulfonated polyetheretherketone, lubricant, antioxidant, dispersant and coupling agent are uniformly mixed by a high-speed mixer, the composite material is modified and granulated by a twin-screw extruder. The twin-screw extrusion temperature is 360-380°C and the extrusion speed is 400r / min to obtain antistatic high-strength polyetheretherketone composite material resin particles.
[0157] The performance tests were carried out on the material samples obtained by injection molding of the above 9 kinds of composite material particles. Before the test, the samples were placed in an environment with a temperature of (23±2)℃ and a relative humidity of (50±5)% for 48h for pretreatment, and then the tensile performance test was carried out according to GB / T1040.2-2006, 1A type sample, tensile speed 50mm / min; the bending performance test was carried out according to GB / T 9341-2008; the impact performance test was carried out according to GB / T 1043.1-2008 (1eA); and the volume resistivity test was carried out according to GB / T 15662-1995. The performance test results of the above 9 kinds of composite materials are shown in Table 1.
[0158] Table 1 Performance test results of samples prepared in various embodiments and comparative examples
[0159]
[0160] It can be seen from the data in Table 1 that, compared with Comparative Example 1, Comparative Example 2 has zinc oxide whiskers added alone; and compared with Comparative Example 1, Comparative Example 3 has sulfonated polyetheretherketone added alone. Both implementations can improve the electrical conductivity and mechanical properties of the composite material to a certain extent. However, due to the poor compatibility of oxidized whiskers with the system and the fact that sulfonated polyetheretherketone itself is not an excellent conductive filler, the improvement effect of the two alone on the composite material is limited. Compared with the three comparative examples, Examples 3 to 5 add modified zinc oxide whiskers and sulfonated polyetheretherketone, which work synergistically to significantly improve the electrical conductivity and mechanical properties of the composite material. Compared with Examples 3 to 5, the mass fractions of each component in Examples 1 and 2 are within the preferred range. Compared with Example 1, Example 6 shows that when the degree of sulfonation of sulfonated polyetheretherketone is 40-50%, the composite material has a more obvious improvement.
[0161] Finally, it should be noted that the various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referred to each other. For the system or device disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part description.
[0162] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present application.
Claims
1. A polyetheretherketone composite material, characterized in that: The composition includes the following components in parts by weight: 50-80 parts of polyetheretherketone resin, 5-25 parts of modified zinc oxide whisker, 5-25 parts of sulfonated polyetheretherketone, 5-30 parts of glass fiber, 5-30 parts of aramid fiber, 0.1-1 parts of lubricant, 0.1-1 parts of antioxidant, 0.1-1 parts of dispersant and 0.1-1 parts of coupling agent.
2. The polyetheretherketone composite material according to claim 1, characterized in that: The composition includes the following components in parts by weight: 60-70 parts of polyetheretherketone resin, 10-15 parts of modified zinc oxide whisker, 5-10 parts of sulfonated polyetheretherketone, 5-20 parts of glass fiber, 5-20 parts of aramid fiber, 0.1-1 parts of lubricant, 0.1-1 parts of antioxidant, 0.1-1 parts of dispersant and 0.1-1 parts of coupling agent.
3. The polyetheretherketone composite material according to claim 1, characterized in that: The modified zinc oxide whisker is prepared by modifying the zinc oxide whisker with a coupling agent; wherein the coupling agent is a coupling agent containing an amino group.
4. The polyetheretherketone composite material according to claim 1, characterized in that: The polyetheretherketone resin has a crystallinity of 20-40% and a melting index of 20-100 g / 10 min at 5 kg / 380° C.
5. The polyetheretherketone composite material according to claim 1, characterized in that: The modified zinc oxide whisker has a root diameter of 0.5-5 μm, an aspect ratio of 10-40:1, and an apparent density of 0.1-0.3 g / cm 3 .
6. The polyetheretherketone composite material according to claim 1, characterized in that: The sulfonation degree of the sulfonated polyetheretherketone is 40-50%.
7. The polyetheretherketone composite material according to claim 1, characterized in that: The glass fiber is short alkali-free glass fiber with a diameter of 10-13 μm, an average length of 0.1-5 mm, and a surface coated with a silane coupling agent; The aramid fiber is aramid 1313, has a diameter of 10-15 μm, an average length of 0.1-3 mm, and is coated with a silane coupling agent.
8. The polyetheretherketone composite material according to claim 1, characterized in that: The lubricant is one or more of calcium stearate, PETS, EBS, and ethylene wax; The antioxidant is one or more of 1,3,5-tris(3,5-di-tert-butyl, 4-hydroxybenzyl)-s-triazine, 4,4'-thiobis(6-tert-butyl-3-methylphenol), and di(octadecyl)thiodipropionate; The dispersant is one or more of montan wax, oxidized polyethylene wax, silicone powder, etc.; The coupling agent is a silane coupling agent.
9. A method for preparing the polyetheretherketone composite material according to any one of claims 3 to 8, characterized in that: The following steps are involved: S1: Modifying zinc oxide whiskers with an amino coupling agent to obtain modified zinc oxide whiskers; S2: Sulfonating the polyetheretherketone to obtain sulfonated polyetheretherketone; S3: The prepared modified zinc oxide whiskers and sulfonated polyetheretherketone are used to prepare conductive polyetheretherketone masterbatch with polyetheretherketone resin, lubricant, antioxidant and dispersant; S4: melt-extrude and granulate the prepared conductive polyetheretherketone masterbatch, polyetheretherketone resin, sulfonated polyetheretherketone, glass fiber, aramid fiber, lubricant, antioxidant, dispersant and coupling agent to obtain a polyetheretherketone composite material.
10. Use of the polyetheretherketone composite material according to any one of claims 1 to 8 or the polyetheretherketone composite material prepared by the method according to claim 9, characterized in that: The polyetheretherketone composite material is used in the fields of automobile, aerospace, electrical and electronic, chemical industry and machinery.